Многолетний мониторинг поселений большого баклана (Phalacrocorax carbo) на морских заливах Северного Причерноморья - Руденко, А.Г.; Ардамацкая, Т.Б.; Яремченко, О.А. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2008)
This paper presents materials of a long-term monitoring of colonies of the Cormorant (Phalacrocorax carbo), nesting on islands of three bays of the Black Sea (Tendrovsky, Yagorlytsky and Dzharylgachsky Bays). Researches have been carried out from the end of 1980s to the present time.